The Effect of Wear and Soil Compaction on Kentucky Bluegrass Sod Rooting and Plant Recovery. Issue 1 (19th October 2017) - Dest, William M.; Ebdon, J. Scott
Abstract : Damage areas in sport fields from wear are often sodded before complete rooting. The objective of this study was to examine the influence of traffic (the combined effects of wear and soil compaction) on sod rooting. Poa pratensis L. sod was installed in September 2008 and 2009 on a silt loam and a sand rootzone at the University of Massachusetts‐Amherst. Treatments included a compaction and noncompaction soil and wear and nonwear treatments, which were evaluated under the influence of two soils. Compaction was applied using a plate Vibro‐Tamper prior to sodding and wear was applied with a steel brush. Wear was initiated 4 wk after sod installation in both years and applied six times. Wear injury and recovery was assessed using a 1 to 9 rating scale (9 = no injury), root initiations were measured by counts, and sod rooting strength was determined by lifting force. Wear significantly reduced sod rooting strength compared with nonwear. New root initiations and root biomass were significantly reduced by wear. Soil compaction significantly reduced root biomass below 7.5‐cm soil depth with no effect observed at the 0‐ to 7.5‐cm depth. Wear applied to sod on the silt loam achieved full recovery 45 d earlier in both years than sod grown on the sand rootzone. The effects of traffic on newly placed sod in the repair of damaged areas on athletic fields indicate that wear is the major stress limiting sod rooting, while soil compaction is secondary.